Long-term tolerance of a fractured self-expanding metal stent in a patient with adenoid cystic carcinoma. (2019) - Ho, Sharlene; Goh, Soon Keng; Ng, Alan WK.; Tai, Dessmon YH.; Lim, Albert YH.; Kor, Ai Ching; Sien Zin, Nge Nge; Abisheganaden, John; Verma, Akash
Abstract: Self-expanding metals stent are used for recanalization of malignant CAO. Fracture of such a stent has been described. This prompts its removal. However removal of a metal stent is difficult and can be hazardous. Due to this US FDA advisory was released against their insertion in benign diseases where long life expectancy can expose the patients to the complications of prolonged indwelling time of these stents. We describe a case of adenoid cystic carcinoma who required SEMS placement for tracheal obstruction. However, stent fracture developed soon after its insertion causing patient to cough out stent pieces multiple times. In view of the challenge associated with removal of metal stent fixed to the tracheal walls at its proximal and distal ends, the stent was left in-situ. Patient has tolerated the fractured stent for 1-year and remains on follow-up without any complication or adverse event. This illustrates the long-term tolerance and safety of a fractured stent and helps to allay anxiety associated with this complication.